Sistem Pakar Diagnosa Penyakit Pada Tanaman Kedelai Hijau Menggunakan Metode Teorema Bayes - Rosid, Danu Fajar Nur; Purnomo, A.Sidiq (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
The periodic handling of soybean plant diseases is often overlooked, leading to frequent crop failures. These crop failures cause panic among farmers who are unsure of what to do without an expert’s guidance. Therefore, in this research, the author has developed an expert system using the Bayesian method to detect diseases in soybean plants. This system can provide temporary solutions or handling methods to anticipate crop failures before seeking direct assistance from an expert. The expert system is created as a web-based system with an accuracy rate of 86%.